Comparison of Thermal and Electrical Modalities in the Assessment of Temporal Summation of Pain and Conditioned Pain Modulation - Sean, Monica; Coulombe-Lévêque, Alexia; Bordeleau, Martine; Vincenot, Matthieu; Gendron, Louis; Marchand, Serge; Léonard, Guillaume (Frontiers in Pain Research, 2021)
Temporal summation of pain (TSP) and conditioned pain modulation (CPM) can be measured using a thermode and a cold pressor test (CPT). Unfortunately, these tools are complex, expensive, and are ill-suited for routine clinical assessments. Building on the results from an exploratory study that attempted to use transcutaneous electrical nerve stimulation (TENS) to measure CPM and TSP, the present study assesses whether a “new” TENS protocol can be used instead of the thermode and CPT to measure CPM and TSP. The objective of this study was to compare the thermode/CPT protocol with the new TENS protocol, by (1) measuring the association between the TSP evoked by the two protocols; (2) measuring the association between the CPM evoked by the two protocols; and by (3) assessing whether the two protocols successfully trigger TSP and CPM in a similar number of participants. We assessed TSP and CPM in 50 healthy participants, using our new TENS protocol and a thermode/CPT protocol (repeated measures and randomized order). In the TENS protocol, both the test stimulus (TS) and the conditioning stimulus (CS) were delivered using TENS; in the thermode/CPT protocol, the TS was delivered using a thermode and the CS consisted of a CPT. There was no association between the response evoked by the two protocols, neither for TSP nor for CPM. The number of participants showing TSP [49 with TENS and 29 with thermode (p < 0.001)] and CPM [16 with TENS and 30 with thermode (p = 0.01)] was different in both protocols. Our results suggest that response to one modality does not predict response to the other; as such, TENS cannot be used instead of a thermode/CPT protocol to assess TSP and CPM without significantly affecting the results. Moreover, while at first glance it appears that TENS is more effective than the thermode/CPT protocol to induce TSP, but less so to induce CPM, these results should be interpreted carefully. Indeed, TSP and CPM response appear to be modality-dependent as opposed to an absolute phenomenon, and the two protocols may tap into entirely different mechanisms, especially in the case of TSP.